Improvement of the Organizational Technological Model of the Route Made Up of the Groups of Cars of Different Owners - Panchenko, S.; Ohar, O.; Kuleshov, V.; Kutsenko, M.; Kuleshov, A. (International Journal of Engineering and Technology, 2018)
A route made up of the groups of cars of different owners can be formed in accordance with the technological processes of the station operation by the transport operator, by the operator that owns the rolling stock, by structural or production units of the railways on the access tracks or on the station tracks which are leased by the branch railway lines to cargo owners. Route optimisation uses an estimation function that determines the routing cost based on the automatic operating system data bases and enables to control routing efficiency and other characteristics used further in making a route table with defining function costs. The technology of cargo transport logistic services with the operation sequence starting from the moment of arrival of empty and loaded cars is proposed. A model for determining cost savings in transportation of the route with bulk cargoes from a consignor as a two-stage model of stochastic programming with recursion and random right-hand sides of the restrictions at the Ukrainian railways is proposed.